다양한 환경조건(NaClO₂ 농도, 상대습도, 온도, 시간)에 따른 이산화염소 기체의 발생량 변화 - 이정민(Jeongmin Lee); 이남택(Nam-Teak Lee); 류지훈(Jee-Hoon Ryu) (Han'guk Sikp'um Kwahakhoe Chi = Korean Journal of Food Science and Technology, 2019)
This study was performed to determine the optimum conditions for the production of gaseous chlorine dioxide (ClO2) from aqueous ClO2 (HCl+NaClO2). When 1 N HCl was reacted with various concentrations of NaClO2 (50,000500,000 mg/mL), the highest concentration (695 mg/L) of gaseous ClO2 was obtained from the aqueous ClO2 containing 100,000 µg/mL NaClO2. Next, the effects of relative humidity (RH; 43, 85, and 100%) and temperature (4, 12, and 25ºC) on the production of gaseous ClO2 were investigated. It was observed that the concentration of gaseous ClO2 was increased as RH was decreased, or the temperature was increased. Finally, it was confirmed that the amount of gaseous ClO2 was highly correlated (R2 =0.9546-0.9992) with the volume of aqueous ClO2. The results of this study provide useful information for designing a sanitization program using gaseous ClO2 under various environmental conditions.